2015
DOI: 10.4103/2230-8210.155405
|View full text |Cite
|
Sign up to set email alerts
|

Growth disorders in type 1 diabetes: an Indian experience

Abstract: Though children with type 1 diabetes mellitus (T1DM) are often tall at the time of diagnosis, they may experience growth retardation, pubertal delay or both, which may be due to poor glycemic control, associated diseases or chronic complications. Factors affecting growth include: gender, genetic environment, age at diagnosis, diabetes duration, puberty, metabolic control, and status of growth hormone (GH), insulin-like growth factors (IGFs), and IGF binding proteins (IGFBPs). Insulin regulates expression of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…Virmani mentioned that there is a huge need to better understand the use of non-insulin therapies in Indian communities and traditional medicine approaches and the importance of educating communities about insulin and growth disorders in type 1 diabetes. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virmani mentioned that there is a huge need to better understand the use of non-insulin therapies in Indian communities and traditional medicine approaches and the importance of educating communities about insulin and growth disorders in type 1 diabetes. 7 …”
Section: Discussionmentioning
confidence: 99%
“… 6 Consequences of this life-changing disease is in India still persisting, such as death before diagnosis due to missed diagnosis, poor management because of low awareness and high costs, limited availability of insulin and poor cold chains in rural areas, and limited availability of blood glucose strips. 7 …”
Section: Introductionmentioning
confidence: 99%
“…IGFs' most important role is to aid increase in bone length by regulating growth plate chondrocyte proliferation and maturation. Insulin is considered an essential regulator of this process as adequate insulin concentration is needed to maintain normal serum concentrations of IGFs and IGFBPs and intraportal insulin concentrations, which leads to GH hypersecretion, low circulating IGF and IGFBPs [4,5]. Reduced growth of children with T1D may be due to alterations in GH concentrations causing physiological abnormalities in bone growth [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate insulin concentration is needed to maintain normal serum concentrations of IGFs, and IGFBPs. IGFs had a pivotal role in both muscle and bone turnover with subsequent increase in bone length by regulating growth plate chondrocyte proliferation and maturation[4,5,15]. Earlier studies reported that IGF-1 serve as a significant determinant of height; this has a more substantial influence than glycemic control and insulin level[16].…”
mentioning
confidence: 99%
“…Kluczowe jest dążenie do poprawy wyrównania metabolicznego [28]. Istotne są: młodszy wiek zachorowania, czas trwania choroby, przebieg okresu pokwitania, płeć, metoda insulinoterapii, choroby dodatkowe [23,32].…”
unclassified